CFD Body Force Propeller Model with Blade Rotational Effect - Ping-Chen Wu (Applied Sciences, 2022)
The purpose of this study is to consider propeller geometry and blade rotation in the propeller model in a CFD code. To predict propeller performance, a body force propeller model was developed based on blade element theory and coupled with URANS (unsteady Reynolds-averaged Navier–Stokes) solver CFDSHIP-IOWA V4.5 both implicitly and interactively. The model was executed inside the flow solver every inner iteration. The grid points inside each 2D blade geometry were identified by a numerical search algorithm. To calculate the lift coefficient, the total flow velocities at 25% foil chord length were obtained using the inverse distance weighting interpolation from the RANS solution. The body forces were distributed linearly along the chord length with the maximal value located at the leading edge and zero at the trailing edge. The main achievements are: (1) for a KP505 propeller in an open water condition, the error of the thrust coefficient generally is around or less than 3%, which is a better prediction than the previous model. (2) For a behind-hull condition, the error is about 1%. (3) For an E1619 propeller in an open water condition, the error is around 6%. (4) The blade-to-blade effect and unsteady flow field between blades are sufficiently resolved by the model.